CONTROL BIOLÓGICO DEL OJO DE GALLO (Mycena citricolor Berk. & Curt.) EN CAFÉ CON Trichoderma spp. BAJO CONDICIONES DE LABORATORIO - Pereira Sarmiento, Damarys Geanine (2022)
American leaf spot of coffee is caused by the fungus Mycena citricolor, the main damage it causes is defoliation in coffee plants, affecting their development and production. In the present research, the aim was to identify the incidence and severity of M. citricolor in two places Malacatos and Santa Rufina from Loja province, to identify the morphocultural characteristics of the isolates of M. citricolor and to evaluate the effect of Trichoderma spp. in the control American leaf spot of coffee under laboratory conditions. To determine the incidence I used the formule the Cooke (2006) and for the severity applied the scale of Leal (2011) and Pereira (2021) also, for the characterition of the isolates used seers references by Garcia (2012) and for control American leaf spot of coffee applied 5 isolates of Trichoderma, 4 are of the plant health laboratory and 1 of business product (Biot-Trich), I realized practices duals of M. citricolor y Trichoderma and practices of different concentrations of Trichoderma on the mycelium of M. citricolor. It is conformed to the obtained results, this verified 100 % of incidence of the illness in all the varieties, while that, the mayor percentage of severity presented the varieties Bourbon in Santa Rufina (72 %) and Sarchimor of the Hacienda Cristal (62,28 %). On the other hand, I got three morphotypes of M. citricolor from the six isolates of the coffee varieties; they were groups according with their morphocultural characteristics. With respect to the five isolates Trichoderma applied in cultivate duals, the isolate G8CTM4 was the one that most inhibited the growth of the pathogenic fungus in the three morphotypes of M. citricolor, likewise, the five isolates Trichoderma in the three concentrations grew on the disc of M. citricolor, getting to inhibit the growth of the pathogen. Key words: Characterization, control, M. citricolor, morphotype, Trichoderma.